Factors affecting establishment of an institutional knowledge management culture – a study of organizational vision - Irina Bogdana Pugna; Dana-Maria Boldeanu (Journal of Accounting and Management Information Systems (JAMIS), 2014)
This paper investigates a range of approaches toward developing a Knowledge Management (KM) strategy according to the organizational vision of Romanian companies. Focused on issues which Romanian organizations face with respect to KM, this article centers on how the implementation of KM can be improved, considering both managerial and cultural issues. The data on which this qualitative research is based was obtained from local managers who reflected on aspects related to knowledge and its management within their organizations by fill in a reflection guide which consisted of open questions only. The analysis performed revealed several valuable insights provided through managers' attitudes and behaviors related to knowledge and KM.
Keywords: D83; M14; M15; D23; 650; Knowledge Management (KM); KM culture; KM strategy; KM practices; organizational learning; qualitative analysis